Eksplorasi Pengalaman Pelanggan dan Kualitas Pelayanan di Uragawa Coffee - Bima Aji Putra; Daffaessa Firgie; Muhammad Raviandra Antares (Journal of Management and Creative Business, 2025)
This study explores customer experience and service quality at Uragawa Coffee through a mixed-method approach with digital content analysis. The research aims to identify customer experience dimensions, analyze service gaps, and develop a contextual service quality conceptual model. Utilizing content analysis on 247 digital reviews from various platforms, the study reveals the complexity of customer interactions in contemporary coffee service ecosystems. Findings demonstrate that customer experiences transcend transactional aspects, involving symbolic constructions encompassing product quality, staff responsiveness, and space atmosphere. Millennial and Z generations demand personal, sustainable, and meaningful experiences. Uragawa Coffee successfully creates differentiation through menu innovation, flexible interior design, and empathetic interactions. The research offers managerial implications for developing responsive and adaptive service strategies.